Talent management in Hungarian economic higher education: The Scientific Students' Associations and the Economic Science Section in focus - Bán, Erika; Ilyésné Molnár , Emese; Jármai, Erzsébet Mária; Vágány, Judit Bernadett (Vezetéstudomány / Budapest Management Review, 2023)
In addition to presenting the role and history of the Scientific Student’s Associations Conference (TDK), the aim of the study was to identify the opinions of the national leaders of the TDK, university lecturers at the forefront of talent management, and university students on the significance of this association and activity and its role in talent management, as well as the participation motivations of those involved. Achieving this complex target system was facilitated by the application of several research methods. As a result of this study, the authors can conclude that talent management includes the strengthening of internal motivation, as well as the provision of financial and moral incentives. An important finding is that teacher and student attitudes towards the TDK movement are strongly influenced by the institutional culture as a whole.